2015
DOI: 10.1007/s11010-015-2400-8
|View full text |Cite
|
Sign up to set email alerts
|

Hesperidin ameliorates trichloroethylene-induced nephrotoxicity by abrogation of oxidative stress and apoptosis in wistar rats

Abstract: Trichloroethylene (TCE), a nephrotoxicant is known to cause severe damage to the kidney. In this study, the nephroprotective potential of hesperidin was evaluated against TCE-induced nephrotoxicity in wistar rats. Oral administration of TCE (1000 mg/kg b.wt) for 15 days enhanced renal lipid peroxidation and reduced antioxidant enzymes armoury viz., reduced renal glutathione, glutathione peroxidase, glutathione reductase, glutathione-S-transferase, catalase and superoxide dismutase. It also enhanced the levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 63 publications
5
10
0
Order By: Relevance
“…44 Previous studies have shown that cisplatin treatment decreases CAT activity in kidney tissue. 45,46 Our results are supported in another study by Siddiqi et al 47 They reported that in trichloroethylene-induced nephrotoxicity, kidney CAT activity was significantly increased by hesperidin administration in Wistar rats. Ma et al 44 suggest that CAT and its derivatives inhibit cisplatin-induced nephrotoxicity.…”
Section: 6supporting
confidence: 83%
“…44 Previous studies have shown that cisplatin treatment decreases CAT activity in kidney tissue. 45,46 Our results are supported in another study by Siddiqi et al 47 They reported that in trichloroethylene-induced nephrotoxicity, kidney CAT activity was significantly increased by hesperidin administration in Wistar rats. Ma et al 44 suggest that CAT and its derivatives inhibit cisplatin-induced nephrotoxicity.…”
Section: 6supporting
confidence: 83%
“…By contrast, it can accelerate cell apoptosis (13). Siddiqi et al suggested that hesperidin ameliorates trichloroethylene-induced nephrotoxicity through altering the expression of caspase-3, bax and bcl-2 in Wistar rats (29). The present study indicated that hesperidin significantly prevented the activities of caspase-3 Figure 10.…”
Section: Discussionsupporting
confidence: 46%
“…Siddiqi et al reported that pretreatment with hesperidin as an antioxidant agent considerably reduced lipid peroxidation, elevation of oxidative enzymes level, blood urea and Cr concentrations in rats exposed to TCE. These results indicate that hesperidin can function as a protective agent against TCE caused nephrotoxicity ( 12 ).…”
Section: Introductionmentioning
confidence: 91%
“…Increasing evidences indicated that TCE induced oxidative stress to rat kidney tissue and alter their metabolic functions ( 5 , 8 , 10 - 14 ). Numerous studies have shown that antioxidant agents can protect kidney against TCE-induced toxicity ( 10 , 12 - 14 ). Siddiqi et al reported that pretreatment with hesperidin as an antioxidant agent considerably reduced lipid peroxidation, elevation of oxidative enzymes level, blood urea and Cr concentrations in rats exposed to TCE.…”
Section: Introductionmentioning
confidence: 99%